Temperate livestock production and health - Pandey, A. B. (Indian Farming, 2015)
The IVRI Research Station at Mukteswar, is involved in various research activities through its central facilities like Biotechnology laboratory, Central Instrumentation Unit, Section on Extension education, the agricultural farm and the orchard. The main work is carried out in its Division of Virology and Division of Temperate Animal Husbandary and extension services of education and trainings for technology awareness among farmers is carried out by its Extension Division.